Integrated analysis of gene expression profiles identifies transcription factors potentially involved in psoriasis pathogenesis. Issue 8 (1st March 2019) - Zeng, Fanfan; Liu, Hongbo; Lu, Di; Liu, Qianqian; Chen, Huoying; Zheng, Fang
Abstract: Psoriasis is a common inflammatory skin disease mediated by cells and molecules in both the innate and adaptive immune systems. Recently, gene expression profile analysis revealed a large set of immune‐related differentially expressed genes (DEGs) in psoriasis. However, the associations between these DEGs and their transcriptional regulation mechanisms have not been completely elucidated. In this study, several psoriasis Gene Expression Omnibus data sets were systematically analyzed using bioinformatics tools to uncover important transcription factors (TFs) that regulate the expression of immune‐related DEGs and further enhance our understanding of psoriasis pathogenesis. Common DEGs encoding chemokines, cytokines, antimicrobial peptides, and keratins were identified in psoriasis, and extensive correlations existed among these DEGs. Several common TFs that bind the promoters of the DEGs, including the well‐known signal transducer and activator of transcription 1 (STAT1), STAT3, and nuclear factor κ‐light‐chain‐enhancer of activated B cells (NF‐κB) as well as ETS homologous factor (EHF), Fos‐like antigen 1 (FOSL1), and Forkhead box C1 (FOXC1), which are rarely studied in psoriasis, were also identified. STAT1, EHF, FOSL1, STAT3, and NFKB1 were positively correlated with these DEGs in psoriasis lesions, whereas FOXC1 was negatively correlated with most DEGs. The decreased expression of the DEGs was accompanied by the downregulation of STAT1, EHF, FOSL1, STAT3, and NFKB1 and the upregulation of FOXC1 upon blocking interleukin 17 (IL‐17) or tumor necrosis factor α signaling in psoriasis. Additionally, the downregulation of IL37 in psoriasis was negatively correlated with STAT1 and CXCL10, which are associated with Th1 responses. These results suggest that TFs play an important role in the pathogenesis of psoriasis, and interfering with the activity of key TFs may be a promising therapeutic strategy for psoriasis. Abstract : By systematically analyzing several psoriasis Gene Expression Omnibus data sets using bioinformatics tools, we found that transcription factors that regulate the expression of immune‐related differentially expressed genes play an important role in the pathogenesis of psoriasis.